2023
DOI: 10.3389/fphy.2023.1192270
|View full text |Cite
|
Sign up to set email alerts
|

Sound characteristics of disordered granular disks: effects of contact damping

Abstract: We investigate numerically the sound properties of disordered dense granular packings in two dimensions. Employing linear equations of motion and excluding contact changes from our simulations, we demonstrate time evolution of sinusoidal standing waves of granular disks. We varied the strength of normal and tangential viscous forces between the disks in contact to explore the dependence of sound characteristics such as dispersion relations, attenuation coefficients, and sound speeds on the contact damping. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…6 How packing structure affects dispersion and attenuation in disordered packings is an open question, the answer to which would have obvious implications for marine sediment acoustics as well as other systems. We note a recent paper, 58 which studied standing modes in disordered 2D packings. These authors demonstrated that, even at large P, the disordered packing structure affects the dispersion relation and attenuation (in time) of plane wave modes of plane wave modes.…”
Section: Introductionmentioning
confidence: 96%
“…6 How packing structure affects dispersion and attenuation in disordered packings is an open question, the answer to which would have obvious implications for marine sediment acoustics as well as other systems. We note a recent paper, 58 which studied standing modes in disordered 2D packings. These authors demonstrated that, even at large P, the disordered packing structure affects the dispersion relation and attenuation (in time) of plane wave modes of plane wave modes.…”
Section: Introductionmentioning
confidence: 96%